PENGARUH IKATAN PRIMORDIALISME TERHADAP PERILAKU MEMILIH PEMILIH PEMULA PADA PILKADA DI KECAMATAN GUNUNG TALANG TAHUN 2015 - Hestixia, Retfi; Azhar, Muhammad Ali; Erawan, I Ketut Putra (Jurnal Nawala Politika, 2017)
Tribal equations are often used by legislative candidates to advance at the election as a campaign strategy to be a chance of victory. As a frame,the theory that author used in this research is Sociological Theory by Chicago Madhhab. The research methodology in this research is using descriptive quantitative research method. The findings of the research obtained were the highest number of cross-tabulation of respondent's tribe with the respondent's choice of 59 Caniago clan selected Gusmal and Yulfadri Nurdin, and the second highest of 50 Malay tribesmen chose Gusmal and Yulfadri Nurdin, where Gusmal was with Caniago and Yulfadri Nurdin has Malay tribe. Based on data, it can be concluded that there is a significant influence of primordialism bonds on the behavior of voters choosing a beginner at pilkada simultaneously in Gunung Talang District, Solok Regency, West Sumatera in 2015. Keywords: Tribe, bond of Primordialism, Choosing Behavior, Elections.